Wideband and Low-Loss Mode Scrambler for Few-Mode Fibers Based on Distributed Multiple Point-Loads - Yaping Liu; Yongmin Jung; Zhiqun Yang; Lin Zhang; David Richardson (IEEE Photonics Journal, 2021)
We propose a new type of all-fiber mode scrambler for mode division multiplexed data transmission based on few mode fibers. By randomly placing multiple point-loads along the fiber length, low loss and wideband mode coupling is obtained amongst all the guided modes. The effect of mode coupling is simulated from a single point-load to multiple point-loads with a specific focus on the insertion loss and wavelength dependence. In an exemplar experimental demonstration we present a mode scrambler for step-index two mode fibers incorporating 150 randomly located point-loads. Uniform mode coupling is achieved over the C band with an insertion loss of less than 1 dB.